Technology to improve reliable access to oxygen in Western Uganda: study protocol for a phased implementation trial in neonatal and paediatric wards - Graham Moore; Hamish Graham; Rami Subhi; Sheillah Bagayana; Joseph Mugerwa; David Peake; Eleanor Nakintu; Daniel Murokora; Roger Rassool; Marc Sklar; Bryn Sobott (BMJ Open)
Introduction Oxygen is an essential medicine for children and adults. The current systems for its delivery can be expensive and unreliable in settings where oxygen is most needed. FREO2 Foundation Australia has developed an integrated oxygen system, driven by a mains-powered oxygen concentrator, with the ability to switch automatically between low-pressure oxygen storage device and cylinder oxygen in power interruptions. The aim of this study is to assess the clinical impact and cost-effectiveness of expanding this system to 20 community and district hospitals and level IV facilities in Western Uganda.Methods and analysis This will be a phased implementation with preintervention and postintervention comparison of outcomes. Standardised baseline data collection and needs assessment will be conducted, followed by implementation of the FREO2 Oxygen System in combination with pulse oximetry in 1–2 facilities per month over a 16-month period, with a total 23-month data collection period. The primary outcome will be the proportion of hypoxaemic children receiving oxygen pre and post oxygen system. Secondary outcomes will assess clinical, economic and technical aspects. Pre and post oxygen system primary and secondary outcomes will be compared using regression models and standard tests of significance. Useability will be quantitatively and qualitatively evaluated in terms of acceptability, feasibility and appropriateness, using standardised implementation outcome measure tools.Ethics and dissemination Ethics approval was obtained from Mbarara University of Science and Technology (MUREC 1/7) and the University of Melbourne (2021-14489-13654-2). Outcomes will be presented to the involved facilities, and to representatives of the Ministry of Health, Uganda. Broader dissemination will include publication in peer-reviewed journals and academic conference presentations.Trial registration number ACTRN12621000241831.